Patient demographics, medical factors, treatment modalities and satisfaction at five traditional Chinese medicine practices in Switzerland: A cross-sectional study - Yingchao Liu; Xiaoying Lyu; Saroj K. Pradhan; Yiming Li; Xingfang Liu; Ralf Bauder; Tanja Heggli; Xiaying Wang; Michael Furian (PLoS ONE, 2025)
Background Traditional Chinese Medicine (TCM) is increasingly integrated into healthcare and insurance systems, therefore, it is essential to understand its current status and patients’ perspectives. Methods This cross-sectional study was conducted from January 1st to December 31st, 2023, across five TCM practices in Switzerland. All patients attending their sixth therapy session were invited to complete an electronically anonymized questionnaire covering patient demographics, treatment experiences, and satisfaction. Results A total of 461 patients participated in the survey, with the majority being female (60.1%) and aged 50 years or older (57.4%). Among them, 54.0% reported multiple health conditions, with 32.9% having musculoskeletal disorders and 31.8% suffering from chronic pain as the main reasons for seeking therapy. Most patients received weekly TCM treatments (91.3%), with 50.7% also undergoing conventional therapies. Of the respondents, 50.0% reported full coverage for their TCM therapy costs. Access to TCM was primarily through personal recommendations (44.5%), and 92.2% of patients reported waiting less than 10 minutes before each therapy session. Acupuncture was the predominant treatment (95.7%), with 35.8% receiving additional dietary advice. The overall patient satisfaction rate stood at 96.5%, with 99.5% indicating their intention to continue receiving TCM treatments. Notably, patients with full insurance coverage for TCM treatment costs demonstrated significantly higher treatment satisfaction compared to those with no coverage (odds ratio = 2.42, 95% confidence interval [1.10 to 5.31], p = 0.028). By contrast, other evaluated medical factors did not show statistically significant associations with treatment satisfaction. Conclusion This study revealed that women, patients aged over 50, and individuals with multiple health conditions, particularly musculoskeletal disorders and chronic pain, are more likely to seek regular integrated TCM treatment. Patients reported high levels of satisfaction with TCM, with treatment satisfaction significantly higher among those with full insurance coverage for TCM treatment costs compared to those without coverage. Future research should enroll a broader range of TCM practices and patient populations to enhance the generalizability of these findings and accurately evaluate how insurance coverage influences TCM satisfaction, thereby better addressing patient needs.